Investigation on the phase-based fuzzy logic controller for magnetorheological elastomer vibration absorber. (April 2017) - Liao, Guojiang; Xu, Yangguang; Wei, Fayuan; Ge, Renwei; Wan, Qiang
This article presents a phase-based fuzzy logic controller for magnetorheological elastomer vibration absorber to trace the excitation frequency rapidly. The phase difference between the relative acceleration of the vibration absorber mass and the absolute acceleration of the primary system is used as the input signal of the fuzzy logic controller to calculate the desired magnetic current. Compared with the traditional stiffness control strategy, the proposed controller does not rely on the accurate relationship between the magnetic current and the resonant frequency of the magnetorheological elastomer vibration absorber. Simulation and experiment results demonstrate that the proposed stiffness controller is efficient to make the magnetorheological elastomer vibration absorber trace the excitation frequency rapidly. When the excitation frequency varies, the magnetorheological elastomer vibration absorber can be tuned properly within several seconds.